An action video game for the treatment of amblyopia in children: A feasibility study. (July 2018) - Gambacorta, Christina; Nahum, Mor; Vedamurthy, Indu; Bayliss, Jessica; Jordan, Josh; Bavelier, Daphne; Levi, Dennis M.
Highlights: Playing a custom child friendly action videogame resulted in improved visual acuity. Improvement of 1.4 lines after 20 h compared to more than 100 h of patching. The action videogame approach may be an effective adjunct treatment for amblyopia. Abstract: The gold-standard treatment for childhood amblyopia remains patching or penalizing the fellow eye, resulting in an average of about a one line (0.1 logMAR) improvement in visual acuity following ≈120 h of patching in children 3–8 years old. However, compliance with patching and other treatment options is often poor. In contrast, fast-paced action video games can be highly engaging, and have been shown to yield broad-based improvements in vision and attention in adult amblyopia. Here, we pilot-tested a custom-made action video game to treat children with amblyopia. Twenty-one (n = 21) children (mean age 9.95 ± 3.14 [se]) with unilateral amblyopia (n = 12 anisometropic and n = 9 strabismic) completed 20 h of game play either monocularly, with the fellow eye patched (n = 11), or dichoptically, with reduced contrast to the fellow eye (n = 10). Participants were assessed for visual acuity (VA), stereo acuity and reading speed at baseline, and following 10 and 20 h of play. Additional exploratory analyses examined improvements after 6–10 weeks of completion of training (follow-up). Following 20 h of training, VA improved, on average, by 0.14 logMAR (≈38%) for the dichoptic group and by 0.06 logMAR (≈15%) for the monocular group. Similarly, stereoacuity improved by 0.07 log arcsec (≈17%) following dichoptic training, and by 0.06 log arcsec (≈15%) following monocular training. Across both treatment groups, 7 of the 12 individuals with anisometropic amblyopia showed improvement in stereoacuity, whereas only 1 of the 9 strabismic individuals improved. Most improvements were largely retained at follow-up. Our feasibility study therefore suggests that the action video game approach may be used as an effective adjunct treatment for amblyopia in children, achieving results similar to those of the gold-standard treatment in shorter duration.